Aneurysmal Rupture of a Mesodiverticular Band to a Meckel’s Diverticulum - Christian Sommerhalder; Kenneth R. Fretwell; Gregory G. Salzler; John M. Creasy; R. Jonathan Robitsek; Sebastian D. Schubl (Case Reports in Surgery)
Aneurysmal rupture of a mesodiverticular band has not previously been reported in the clinical literature. We are reporting a case of hemoperitoneum in a 51-year-old male after an aneurysmal rupture of a mesodiverticular band. This case demonstrates that in rare instances, a rupture of the mesodiverticular band leading to Meckel’s diverticulum can lead to significant hemoperitoneum. This is usually caused by a traumatic injury but in our case was apparently caused by an aneurysm of the mesodiverticular artery. Patients with known Meckel’s diverticula should be aware of the possibility of rupture, as should clinicians treating those with a history of this usually benign congenital abnormality. Rapid surgical intervention is necessary to repair the source of bleeding, as massive blood loss was encountered in this case.